Calculated mixing enthalpies of 11 IIB-IVB and IIB-VB binary alloy systems using a subregular model - Bangwei Z.; Xiaolin S.; Shuzhi L.; Xiaojian Y.; Haowen X. (Journal of Mining and Metallurgy. Section B: Metallurgy)
There have been no theoretical calculations of the mixing enthalpies for group B metal alloy systems using the famous Miedema theory or from first principles. Therefore such systematic calculations for the 11 group IIB－IVB and IIB－VB binary alloy systems are performed for the first time using a subregular model. The results show that the agreement between the calculations and experimental data is pretty good and could be accepted from the theoretical or experimental points of view. It can be concluded from the results that the subregular model can be used for calculating the mixing enthalpies of the group B alloy systems, at least for the IIB－IVB and IIB－VB alloy systems.